2005
DOI: 10.1021/jp050626h
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Properties of the Oxime Analogue of Glycine to Cu(II)

Abstract: The coordination of Cu2+ by glyoxilic acid oxime (gao)--the oxime analogue of glycine amino acid--and its deprotonated (gao- and gao2-) species has been studied with different density functional methods. Single-point calculations have also been carried out at the single- and double- (triple) excitation coupled-cluster (CCSD(T)) level of theory. The isomers studied involve coordination of Cu2+ to electron-rich sites (O,N) of neutral, anionic, and dianionic gao species in different conformations. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 46 publications
(92 reference statements)
1
40
0
Order By: Relevance
“…Consistently, no covalent bonds between Ca and the serine basic centers are found in the NBO analysis, whereas the The partially covalent character of the interactions with Cu is also reflected in the electron density at the corresponding BCPs, which are about twice as large as those calculated for the corresponding Ca 2+ complex. 52 Conversely, the behavior of calcium towards serine is quite similar to that exhibited towards uracil, 53 thiouracils, 53 urea, and thiourea. The significant differences in the reorganization of the electron density of the serine, when interacting with Cu 2+ and Ca 2+ , have their origin in the huge difference between the recombination energy for both dications (20.29 eV for Cu 2+ but only 12.03 eV for Ca 2+ ).…”
Section: Resultsmentioning
confidence: 83%
“…Consistently, no covalent bonds between Ca and the serine basic centers are found in the NBO analysis, whereas the The partially covalent character of the interactions with Cu is also reflected in the electron density at the corresponding BCPs, which are about twice as large as those calculated for the corresponding Ca 2+ complex. 52 Conversely, the behavior of calcium towards serine is quite similar to that exhibited towards uracil, 53 thiouracils, 53 urea, and thiourea. The significant differences in the reorganization of the electron density of the serine, when interacting with Cu 2+ and Ca 2+ , have their origin in the huge difference between the recombination energy for both dications (20.29 eV for Cu 2+ but only 12.03 eV for Ca 2+ ).…”
Section: Resultsmentioning
confidence: 83%
“…The application of the B3LYP method to metal ion-water systems has proved a reasonable success. [52][53][54][55] For open-shell Cu 2+ -ligand systems with low coordination numbers (n ) 1, 2) it has been reported [56][57][58] that B3LYP binding energies are overestimated compared to CCSD(T) results. However, the B3LYP relative energies for systems with similar spin density distribution are in good agreement with those determined by highly correlated electronic structure methods.…”
Section: Methodsmentioning
confidence: 99%
“…Density functional methods have been shown to be cost-effective methods and have been used to study a wide variety of closed-shell systems with great accuracy (Koch & Holthausen 2001;Sholl & Steckel 2009;Sousa et al 2007). However, for open-shell systems, calculations carried out by some of us have demonstrated that functionals with a larger percentage of exact exchange, such as BHLYP, provide better results compared to the highly correlated CCSD(T) method (Georgieva et al 2005;Poater et al 2004;Rimola et al 2006;Sodupe et al 1999). This is due to the fact that GGA or hybrid functionals with small percentages of exact exchange such as B3LYP overstabilize too delocalized situations, as a result of a bad cancellation of the self-interaction part by the exchange-correlation functional.…”
Section: Computational Detailsmentioning
confidence: 99%